What are the determinants of non-performing loans in Botswana? - Tsumake, Gertrude Kgalalelo (Department of Finance and Tax, 2017)
The maintenance of asset quality, efficiency and profitability is a vital requirement for the survival and development of banks. Loans are the main asset class from which banks generate their major portion of income and also signify the greatest risk to banks. There has been significant indication that the financial crises in the USA, Sub-Saharan Africa and East Asia were signalled by high levels of non-performing loans (NPLs). Due to the detrimental effect that these loans have on a bank's revenue and the economic welfare of a country, it is essential to examine and investigate the determinants of NPLs in the banking industry of any country. This study examines Botswana, a developing country in Southern-Africa and is stimulated by the assumption that both the industry level variables and macroeconomic variables have an effect on NPLs. Secondary data of the banking sector was obtained from Botswana's central bank, the Bank of Botswana. Correlation and regression analysis were carried out over a period of ten years (2005-2014), using quarterly data. It was found that the following industry level variables (i.e. credit growth, industry size and profitability) and macroeconomic variables (i.e. real gross domestic product (GDP) growth, inflation, real interest rates and the unemployment rate) have a statistically significant impact on the NPL rate. On the other hand, capitalization and diversification had a statistically insignificant relationship with NPLs. The banking industry in Botswana should carefully monitor the household loan portfolio as well as their credit advancement policies with regard to the aforementioned variables to help lower their NPL ratios. This study is the first of its kind in the Botswana banking industry and therefore will provide scholars with the opportunity to enrich their knowledge and serve as a reference for other researchers in the related area while also providing a foundation for further studies.